Penerapan Konsep Plea Bargaining Dalam Sistem Peradilan Pidana Terpadu Di Indonesia - Paklioy, Ronny Putra Dirgantara; Titahelu, Juanrico Alfaromona Sumarezs; Latumaerissa, Denny (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The principle of simple, fast and low cost justice is a principle in the Indonesian judicial system that requires the implementation of law enforcement to be able to provide protection and legal certainty in the judicial process. The plea bargaining system is one of the alternatives that can be used to overcome the burden of cases in court and realize the principle of simple, fast and low cost justice as a principle in the Indonesian criminal justice system optimally.Purposes of the Research: The purpose of this paper is to review and analyze the application of the plea bargaining system and the obstacles in the application of the plea bargaining system in the Indonesian justice system.Methods of the Research: The method used in this writing is normative juridical with a statutory approach, comparative approach, and concept approach.Results of the Research: Based on this paper, it can be concluded that plea bargaining system is a part of criminal justice system that is developed and maintained by many countries up to now, both countries with common law system and countries with civil law system. Plea bargaining system is a system that has not been recognized in the Indonesian judicial system, however, this system can be a solution to the problem of accumulation of cases in the courts, the implementation process must be carried out comprehensively, and adjustments need to be made to the Indonesian criminal justice system so that it can be implemented and implemented optimally and effectively.